Relationship between rowing ergometer performance and physiological responses to upper and lower body exercises in rowers - Jürimäe, T.; Perez-Turpin, J. A.; Cortell-Tormo, J. M.; Chinchilla-Mira, I. J.; Cejuela-Anta, R.; Mäestu, J.; Purge, P.; Jürimäe, J. (Journal of Science and Medicine in Sport, 2010)
The aim of this investigation was to compare the physiological responses of 2000 m rowing ergometer test with 7-min bench pull and leg press tests. We hypothesised that leg press exercise contributes to 2000 m rowing ergometer test results, rather than bench pull performed by arms. College level rowers (n = 12) performed 2000 m rowing test and after one day 7-min bench pull and leg press (50% from the 1 RM). Stroke rate, heart rate (HR), blood lactate (LA) and ratings of perceived exertion (RPE) were measured during all tests. The number of repetitions was highest during 2000 m rowing test (194.2 ± 19.5) and lowest during bench pull (122.6 ± 17.7) (during leg press 173.5 ± 11.8). Differences between 2000 m rowing test, leg press and bench pull tests were significant in mean and maximal HR. In LA concentration, the highest values were at 3rd min of recovery after rowing test (14.8 ± 1.7 mmol l-1). Between bench pull (8.8 ± 1.9 and 8.5 ± 2.7 mmol l-1) and leg press (11.8 ± 2.5 and 11.2 ± 2.3 mmol l-1) tests, the difference in LA concentration was not significant (p > 0.05). Ratings of perceived exertion were highest in 2000 m rowing test (19.3 ± 0.9), difference with leg press and bench pull tests was not significant. There were significant relationships in mean and maximal HR (r = 0.713-0.767) and Borg scale (r = 0.764) during rowing test and leg press. The number of repetitions during leg press exercise correlated significantly with rowing test time (r = -0.677). In conclusion, this study suggests that in rowers there are major differences in the physiological adaptation to upper body and leg exercise, performed at similar intensities. Leg press exercise could be used to measure sport-specific strength endurance in rowers.